The influence of superplasticiser on mechanical, transport and microstructure properties of foam concrete - Abdullah Al-Shwaiter; Hanizam Awang; Mohammed A. Khalaf (Journal of King Saud University: Engineering Sciences, 2023)
Superplasticiser (SP) is widely used in foam concrete industry to improve rheological properties since compaction and vibration adversely affect the stability of foam bubbles. This study aims to investigate the effect of polycarboxylate SP contents on the properties of foam concrete. Different water-cement ratios (w/c) were used, and the SP added to the mixture to adjust the spreadability. The density of 1500 kg/m3 was chosen for the production of foam concrete for semi-structural applications. Fresh, mechanical, transport and microstructure properties were analysed in this study. The results of this study showed that the content of w/c and SP had a significant impact on the performance of the foam concrete. Increasing the SP content enhanced the foam concrete’s mechanical and transport properties, but the best behaviour was through the use of 1.35% of SP. Smaller pore diameter, better pore distribution and higher portlandite peak intensity were achieved through the use of the SP. Overall, the superior behaviour of the foam concrete was achieved by the use of 1.35% polycarboxylate SP.